Transcriptional Profiling of Myceliophthora thermophila on Galactose and Metabolic Engineering for Improved Galactose Utilization - Wang, Hanyu; Sun, Tao; Zhao, Zhen; Gu, Shuying; Liu, Qian; Wu, Taju; Wang, Depei; Tian, Chaoguang; Li, Jingen (Frontiers in Microbiology, 2021)
Efficient biological conversion of all sugars from lignocellulosic biomass is necessary for cost-effective production of biofuels and commodity chemicals. Galactose is one of the most abundant sugar in many hemicelluloses and it will be important to capture this carbon for an efficient bioconversion process of plant biomass. Thermophilic fungus Myceliophthora thermophila has been used as cell factory to produce biochemicals directly from renewable polysaccharides. In this study, we draw out the two native galactose utilization pathways, including the Leloir pathway and oxido-reductive pathway, and identify the significance and contribution of them, through transcriptional profiling analysis of M. thermophila and its mutants on galactose. We find that galactokinase was necessary for galactose transporter expression, and disruption of galK resulted in decreased galactose utilization. Through the metabolic engineering, both of galactokinase deletion and galactose transporter overexpression can activate internal the oxido-reductive pathway and improve consumption rate of galactose. Finally, the heterologous galactose-degradation pathway, De Ley-Doudoroff pathway, was successfully integrated into M. thermophila and the consumption rate of galactose in the engineered strain was increased by 57%. Our study focuses on metabolic engineering for accelerating galactose utilization in thermophilic fungus will be benefit for the rational design of fungal strains to produce biofuels and biochemicals from a variety of feedstocks with abundant of galactose.